HOW RISK FACTORS SIGNIFICANTLY AFFECT THE INCIDENCE OF TYPE 2 DIABETES MELLITUS IN TARUS, KUPANG - Harsa, I Made Subhawa; Masneno, Prisilia Christin Velisites; Setijowati, Eva Diah; Al Aska, Andra Agnez (Folia Medica Indonesiana, 2025)
The incidence of type 2 diabetes mellitus (T2DM) is influenced by both unmodifiable factors, such as age, family history, education, and employment status, as well as modifiable factors, including obesity, diet, physical activity, and smoking habits. Researchers have recognized the necessity of research on risk factors for T2DM across various regions. However, the findings have been inconsistent. The absence of research on risk factors for T2DM in some regions has necessitated the conduct of studies in these areas, particularly in primary health care facilities such as Community Health Centers (Puskesmas). This study aims to control the risk factors that contribute to the incidence of diabetes mellitus. This study is an observational study with a cross-sectional research approach. The study comprised a sample of 97 respondents who met the study inclusion and exclusion criteria selected from all residents of Kupang City domiciled in the working area of the Tarus Community Health Center, Kupang City. This study employed the Chi-square test to conduct the data analysis. This study revealed a correlation between age, family history, and exposure to cigarette smoke with the incidence of T2DM. However, the authors did not find any correlation between gender, physical activity, diet, and alcohol consumption and the incidence of diabetes mellitus. The study concluded that the primary factor associated with the incidence of diabetes mellitus was a family history of Type 2 diabetes mellitus (T2DM).